EFEKTIVITAS PEMBELAJARAN MATEMATIKA MELALUI PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) PADA SISWA KELAS VII SMP ISLAM TERPADU AL HIKMAH KABUPATEN PANGKEP - Resmi Resmi; Ahmad Syamsuadi; Randy Saputra Mahmud; Fathrul Ariah (Universitas Muhammadiyah Makassar, 2022)
This research is a pre-experimental study involving an experimental class which aims to determine the effectiveness of learning through the Contextual Teaching and Learning (CTL) Approach in learning mathematics in class VII students of Al Hikmah Integrated Islamic Middle School, Pangkep Regency, 2021/2022 academic year. While the effectiveness of learning is viewed from three aspects, namely: the implementation of learning, classical learning completeness, student activity, and student responses. A learning is said to be effective if at least three of the four aspects above are met, provided that aspects of student activity and classical learning mastery are met. Student scores after learning mathematics through the application of the Contextual Teaching and Learning approach have achieved classical mastery. The average positive student activity is 85.7% and 12.5% negative, this indicates that student activity in learning mathematics through the Contextual Teaching and Learning approach can be said to be active. Student responses to learning the Contextual Teaching and Learning approach can be said to be in accordance with the standards set, namely exceeding 75% of students who gave a positive response. Based on the results of descriptive and inferential analysis, it shows that student learning outcomes before learning the Contextual Teaching and Learning approach are smaller than student learning outcomes after learning the Contextual Teaching and Learning approach, thus learning mathematics through the Contextual Teaching and Learning approach is effectively used on the subject of Algebra in class students VII Al Hikmah Integrated Islamic Middle School, Pangkep Regency.